Auditory Mirror Therapy for Tinnitus: A Pilot Study - Linnman, Clas (Journal of the American Academy of Audiology, 2022)
Background Tinnitus, the phantom perception of sound, shares many properties with phantom limb pain, in that both may arise as a consequence of sensory deprivation. Prediction errors in multisensory integration, such as induced with mirror box therapy in phantom pain, can reduce phantom percepts.Purpose We evaluated if a device that swaps sound from the right pinna to the left ear canal, and from the left pinna to the right ear canal, can reduce tinnitus. We call this auditory mirror therapy (AMT).Research Design Uncontrolled trial.Study Sample Twenty subjects with chronic tinnitus.Intervention An AMT device consisting of a modified ear defender device with microphones that swaps sounds from left pinna to the right ear canal and from the right pinna to the left ear canal. Participants used the device at home for 2 weeks.Data Collection and Analysis Tinnitus Handicap Inventory (THI), Tinnitus Reaction Questionnaire, and visual analog scale ratings of symptoms were collected at baseline and posttreatment. Repeated measures t-test were performed, Bonferroni corrected for multiple comparisons.Results There was a significant reduction in THI and in awareness of tinnitus after the AMT intervention.Conclusion Exposing the audiovisual integration system to prediction errors can help retrain phantom percepts and reduce tinnitus handicap. Further studies on this concept are warranted.
Keywords: tinnitus; mirror box therapy; pseudophone; multisensory integration